HOSPITAL BOARD COMPETENCIES SUPPORTING QUALITY GOVERNANCE: A SCOPING REVIEW - Aniza Winanda, Rizky; Wibowo, Adik; Wijaya, Aurelianne; Ayuningtyas, Dumilah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Background: The characteristics of hospital boards determine the output of healthcare quality. Certain sets of skills, composition, and dynamics make up for the competencies required of hospital boards in order to assure healthcare services are safe. Aims: The objective of this scoping review is to determine competencies required of hospital boards that not only have a role in assuring healthcare quality, but also serve as general qualifications for best practice.Methods: A scoping review was conducted through searching three electronic databases including relevant terms for the following concepts: hospital board and its required competencies. Grey literature was included to introduce a variety of perspectives on the subject and support an enriched discussion. Results: 16 articles were included in this review. The majority of studies were qualitative studies with a focus on evaluating behavioral dynamics of hospital boards and its effect on healthcare quality governance. Three main themes of hospital board competencies include individual board member attributes, team dynamics, and organizational outcome. Conclusion: Studies had different definitions of whom the term hospital board or governing board refers to, creating difficulty in formulating a certain set of essential qualities. A medical background is found to have positive associations with performance on care quality and patient safety practices.